Study of Degree of Lumbar Wedging Measured Using CR- 35X Digitizer - Vinay, KV; Vinay, HS; Vishal, K (Nepal Journal of Medical Sciences, 2013)
Background: Low back pain is a very common symptom. Population based normal variations of lumbar wedging (LW) in South Indian population is not well documented in literature. This study was done to compile a database of LW valid for healthy male and female subjects in the age range of 20-60 years in South Indian population. Methods: The plain lateral radiographs of lumbar spine of 150 healthy subjects (88 males and 62 females) between 20 to 60 years were studied. The lumbar vertebral body height anteriorly (HBA) and posteriorly (HBP) were measured using CR-35X digitizer. The degree of LW was determined by the ratio of HBA /HBP. Results: There was a gradual decrease in LW cranio-caudally from L1 to L5 in both sexes being maximum at L1 (0.96 in males and 0.97 in females) and minimum at L5 (1.13 in males and 1.13 in females). LW was higher in males than in females. LW is statistically significant only at L3 level and non significant at all other levels. Positive relationship of LW to age was not found. Conclusion: The study provide the best available estimates of normal LW for the South Indian healthy subjects, which will be helpful to the clinicians, therapists and researchers as ready references to LW in South Indian population. Nepal Journal of Medical Sciences | Volume 02 | Number 01 | Jan-Jun 2013 | Page 30-33 DOI: http://dx.doi.org/10.3126/njms.v2i1.7648